PERBANDINGAN TINGKAT LOYALITAS TERHADAP MEREK PADA PENGGUNA SMARTPHONE BERDASARKAN TEORI KEPRIBADIAN BIG FIVE FACTORS OF PERSONALITY - Herdiyan Maulana; Rury Siti Ruhaniah (UIN Sunan Kalijaga, 2013)
This study aims to explore whether there is comparative of brand loyalty degree based on theory Big Five Factors of Personality on smart-phone user. Research conducted by involving 142 smartphone users that settle in Jakarta. Instruments that used in this study consisting of two research scale, the level of brand loyalty scale and personality scale that adopted from personality scale of International Personality Item Pool (IPIP) which based on NEO-PI R. Hypotheses tested by chi square analyze with the assistance program SPSS version 17.0 for Windows. Based on the analysis result of data that has been done obtained chi square of personality variable is 58,070, degree of freedom is 4 with p-value 0.00 < 0.05, chi square of brand loyalty level variable is 15,958, degree of freedom is 4 with p-value 0.03 < 0.05. This means that the null hypothesis is rejected and the alternative hypothesis is accepted, then there is a signifcant comparison of levels of brand loyalty based on the theory the Big Five Factors of Personality on the smartphone user.